2023
DOI: 10.3389/fcimb.2023.1119020
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing urinary tract infection diagnosis for negative culture patients with metagenomic next-generation sequencing (mNGS)

Abstract: BackgroundMetagenomic next-generation sequencing (mNGS) is a promising technology that allows unbiased pathogen detection and is increasingly being used for clinical diagnoses. However, its application in urinary tract infection (UTI) is still scarce.MethodsThe medical records of 33 patients with suspected UTI who were admitted to the Second Hospital of Tianjin Medical University from March 2021 to July 2022 and received urine mNGS were retrospectively analyzed. The performance of mNGS and conventional urine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Polymicrobial infections with more than two pathogens are usually considered contamination under the current SOC and reporting of these results as infection is a topic of debate (18). In accordance with other UTI studies employing molecular approaches, about 40 % of clinical specimens tested in this validation showed more than one pathogen detected (83, 85, 89–92). Most clinical algorithms designed for uropathogen detection provide optimal growth conditions for a limited number of microbes and are based on a threshold of 10 5 CFU/mL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Polymicrobial infections with more than two pathogens are usually considered contamination under the current SOC and reporting of these results as infection is a topic of debate (18). In accordance with other UTI studies employing molecular approaches, about 40 % of clinical specimens tested in this validation showed more than one pathogen detected (83, 85, 89–92). Most clinical algorithms designed for uropathogen detection provide optimal growth conditions for a limited number of microbes and are based on a threshold of 10 5 CFU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Like other molecular-based studies, BIOTIA-ID showed increased detection of atypical pathogens including Candida, G. vaginalis, Aerococcus spp., anaerobic bacteria (Prevotella spp.) and fastidious bacteria, organisms not reported with culture-based diagnostics (30,(82)(83)(84)(85). Although the rise of molecular based diagnostics and clinical studies using these technologies have revealed that gram-positive, atypical, or fastidious pathogens account for a larger percentage of cUTI infections, more interventional, and clinical utilization studies are needed to understand the pathogenesis and epidemiology of these understudied microbes (19,62,(86)(87)(88).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the performance of mNGS and conventional urine culture in the diagnosis of infection and identification of pathogenic microorganisms, it was found that the detection rate and sensitivity of mNGS were significantly higher than that of culture. In addition, mNGS detected a wider range of pathogens [ 13 ]. In a study on 641 patients with infectious diseases, by comparing the detection efficiency of mNGS and traditional culture method for different pathogens, the positive rate of mNGS was 69.89 %, significantly higher than that of traditional culture 22.31 % [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to urine, in a single centre study of 33 patients from China, mNGS detected at least 1 pathogen in 29 (97.9%) cases, of which four instances of fungus (3 species-Talaromcyes marneffei, C. parapsilosis and C. albicans twice) were identified [216].…”
Section: Other Specimensmentioning
confidence: 99%